Sympathetic Nerve Function Status in Follicular and Late Luteal Phases of Menstrual Cycle in Healthy Young Women - Choudhury, Rama; Jahan, Nasim; Sultana, Nayma; Akter, Rezina; Khanum, Ayesha Akhter (Journal of Bangladesh Society of Physiologist, 2011)
Background: Autonomic nerve function status may be changed during follicular and late luteal phases of menstrual cycle due to fluctuations of serum estrogen and progesterone level. Objective: To observe the sympathetic nerve function status during follicular and late luteal phases of menstrual cycle and their relationships with serum estrogen and progesterone in healthy young womens. Methods: This cross-sectional study was carried out in the Department of Physiology, Sir Salimullah Medical College, Dhaka from 1st January 2009 to 31st December 2009.A total number of thirty (30) apparently healthy unmarried women with age ranged from 20-25 years were investigated. Two simple autonomic nerve function tests, like fall of systolic blood pressure (SBP) on standing and rise of diastolic blood pressure (DBP) during handgrip were done to assess sympathetic activity. Serum estrogen and progesterone levels were also measured by AxSYM method. All these tests were performed in both follicular and late luteal phases of menstrual cycle. Data were analysed by paired student’s ‘t’ test and Pearson’s correlation coefficient test as applicable. Results: Mean resting heart rate was significantly (p<0.01) increased in late luteal phase than that of follicular phase. Mean resting systolic blood pressure was significantly (p<0.01) increased and resting diastolic blood pressure was non-significantly increased in late luteal phase than those of follicular phase. Again, significantly (p<0.05) increased value of fall of systolic blood pressure after standing from lying and non-significant increased value of rise in diastolic blood pressure after sustained handgrip were observed in late luteal phase. The mean value of serum estrogen was non-significantly and serum progesterone was significantly (p<0.001) increased in late luteal phase than those of follicular phase. Conclusion: From this study it can be concluded that sympathetic activity is increased in late luteal phase of menstrual cycle. In addition, increased sympathetic activity during late luteal phase might be the cause of premenstrual syndrome (PMS) in some women. Key words: Sympathetic nerve functions; progesterone. DOI: 10.3329/jbsp.v5i2.6782 J Bangladesh Soc Physiol. 2010 December; 5(2): 80-88